Does International Accreditation Provide for Greater Enrolment, Program Completion, Employment, and Employer Satisfaction? - Paul (Sr.), Stanley A. V.; English, Ivor B.; Gjorgov, Emil; Paul (Jr.), Stanley A. V.; Rajkumar, Yogita (Integrated Journal for Research in Arts and Humanities, 2023)
Aim: The current research was conducted to examine the potential influence of international accreditation of universities on the enhancement of students’ enrolment and educational quality, employment opportunities, and employer satisfaction. The study also contextualized the findings to focus on the case of Guyana. Methodology: A secondary qualitative research methodology was used to conduct this research. It comprised using an inductive approach to gather and study the most contemporary and relevant secondary literature on the subject. Afterward, through thematic analysis, major qualitative finding and their patterns were segmented in the form of two major themes. Findings: This study discovered that international accreditation benefits both business satisfaction and student satisfaction. It was discovered that the planning and self-study evaluation activities for accreditation operate as a catalyst for quality improvement practices. The results also imply that consistent efforts to satisfy requirements for international accreditation can raise the level of instruction given to pupils. It is yet unknown, though, how certification will impact Guyana's employment prospects and employee happiness.